Correlation of oxidative stress with serum essential elements level in beta thalassaemia major patients in Sabah - Shazia Qaiser (2015)
Beta thalassaemia major is one of the leading public health problems in Malaysia affecting significant number of infants born each year. It is the severe form of beta thalassaemia resulting from homozygosity for the phenotype β0 (β0β0). Although repeated blood transfusions are obligatory for the survival of beta thalassaemia major patients, it also accelerates oxidative stress secondary to iron overload. This study aims to determine the correlation between oxidative stress and serum essential elements level in beta thalassemia major patients. One hundred randomly selected transfusion dependent beta thalassaemia major patients on chelation therapy and one hundred non thalassaemic healthy controls were included in this study. Essential elements were estimated by using Flame atomic absorption spectrophotometer (FAAS) while oxidative stress markers were determined using dual beam spectrophotometer. Statistical analysis of the data was performed using independent t-test and Pearson’s correlation analysis. The p-value < 0.05 is considered statistically significant in this research. In the present study, significantly decreased (p< 0.05) serum concentrations of zinc (Zn) and magnesium (Mg) while significantly increased (p< 0.05) serum concentrations of manganese (Mn) and chromium (Cr) were found in beta thalassaemia major patients as compared to the controls. The serum levels of copper (Cu) and potassium (K) remain unchanged. In addition, the serum levels of reduced glutathione (GSH) were significantly lower (p< 0.05) while serum levels of glutathione s transferase (GST), catalase (CAT) and lipid peroxidation products (LPO) were significantly higher (p< 0.01) in beta thalassaemia major patients as compared to the healthy counterparts. Interestingly, the age and gender based alteration in levels of serum Mn and CAT activity was also observed. Furthermore the results from the Pearson’s correlation suggest that a significant negative correlation present between serum LPO levels and serum Zn and Mg levels. Moreover, a significant positive correlation was found between serum Mn and serum GST levels in beta thalassaemia major patients. In conclusion, the presence of a correlation between oxidative stress and essential elements was observed in beta thalassaemia major patients. The findings of this study suggest that increased oxidative stress may alter the level of certain essential elements in beta thalassaemia major patients.